The Use of Twitter for Public Education on Stunting in Indonesia - Hidayat, Rachmat (Sustainability Science and Resources, 2022)
Stunting has for decades become a serious development problem in Indonesia. In 2022 President Joko Widodo sets a target of reducing stunting prevalence rate from 30.8% in 2018 to 14% in 2024. A key program in the Indonesian government’s strategies to achieve this goal is a massive public education campaign on stunting. This article provides a review of the communication approach adopted by the government in its social media campaign via Twitter. The results show that various government institutions have adopted the persuasive communcation approach in doing so. A grass-root community survey is needed to assess the campaign’s effectiveness.